2017
DOI: 10.1364/boe.8.003981
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity optical measurement of skin gloss

Abstract: Abstract:We demonstrate a low-cost optical method for measuring the gloss properties with improved sensitivity in the low gloss regime, relevant for skin gloss properties. The gloss estimation method is based on, on the one hand, the slope of the intensity gradient in the transition regime between specular and diffuse reflection and on the other on the sum over the intensities of pixels above threshold, derived from a camera image obtained using unpolarized white light illumination. We demonstrate the improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The second method is based on the number of pixels above a threshold weighted with the corresponding pixel intensity. Further details of the method are described in [7]. The gloss value calculated using the proposed method are compared with the method based on the ratio of the specular to diffuse reflection, used in traditional gloss measurement devices such as Gardner Gloss meter (Micro-Tri-Gloss) and Skin gloss meter (Courage & Khazaka).…”
Section: Image Processing Algorithms For Gloss Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second method is based on the number of pixels above a threshold weighted with the corresponding pixel intensity. Further details of the method are described in [7]. The gloss value calculated using the proposed method are compared with the method based on the ratio of the specular to diffuse reflection, used in traditional gloss measurement devices such as Gardner Gloss meter (Micro-Tri-Gloss) and Skin gloss meter (Courage & Khazaka).…”
Section: Image Processing Algorithms For Gloss Estimationmentioning
confidence: 99%
“…Recently we reported a high sensitivity optical method for measuring skin gloss in the low gloss regime based on number of pixels above a threshold weighted with intensity and slope of the intensity profile in the transition region from specular spot to diffuse background [7]. We have used Monte Carlo ray tracing simulations using the LightTools software to calculate the gloss for a full range samples from 100% specular (mirror) to 100% diffuse (Diffuse standard).…”
Section: Introductionmentioning
confidence: 99%
“…They, respectively, lead to the specular and diffuse reflection of the incident light. Therefore, in the characterisation of skin gloss, specular or diffuse reflectance or their combinations have been used [6], among other methods. Skin gloss is also known to be significantly influenced by the surface roughness, which can sometimes be enhanced after skin rejuvenation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the factors contributing to skin optical properties, skin gloss is also influenced by external factors such as the light source [9,10] (wavelength, intensity and polarization) and measurement geometry [6] in terms of angle of incidence. It has also been demonstrated that lowlevel laser source in the visible or near infrared region presents better light-tissue interactions, especially, in the biological medium than LEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation